Development of Non-Litigation Civil Dispute Settlement Model Based on Madurese Local Wisdom to Reduce Cases Accumulation in Court - Uswatun Hasanah; Mohammad Amir Hamzah; Indien Winarwati (Brawijaya Law Journal, 2019)
Arbitration and other alternative dispute resolution (ADR) can be used as an option for parties who conduct commercial transactions. This research is crucial to analyse what is the best dispute method  for parties to be able to resolve their commercial business disputes. It is argued that the most important of ADR is the efficiency and effectivines in relation to the enforcement of a judgement on the commercial dispute especially foreign arbitral award.